Cultures in Conflict: The Seven Years' War in North America - Hofstra, Warren R. (Rowman & Littlefield Publishers, 2007)
The Seven Years' War (1754–1763) was a pivotal event in the history of the Atlantic world. Perspectives on the significance of the war and its aftermath varied considerably from different cultural vantage points. Northern and western Indians, European imperial authorities, and their colonial counterparts understood and experienced the war (known in the United States as the French and Indian War) in various ways. In many instances the progress of the conflict was charted by cultural differences and the implications participants drew from cultural encounters. It is these cultural encounters, their meaning in the context of the Seven Years' War, and their impact on the war and its diplomatic settlement that are the subjects of this volume. Cultures in Conflict: The Seven Years' War in North America addresses the broad pattern of events that framed this conflict's causes, the intercultural dynamics of its conduct, and its profound impact on subsequent events—most notably the American Revolution and a protracted Anglo-Indian struggle for continental control. Warren R. Hofstra has gathered the best of contemporary scholarship on the war and its social and cultural history. The authors examine the viewpoints of British and French imperial authorities, the issues motivating Indian nations in the Ohio Valley, the matter of why and how French colonists fought, the diplomatic and social world of Iroquois Indians, and the responses of British colonists to the conflict. The result of these efforts is a dynamic historical approach in which cultural context provides a rationale for the well-established military and political narrative of the Seven Years' War. These synthetic and interpretive essays mark out new territory in our understanding of the Seven Years' War as we recognize its 250th anniversary.